(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, the right of His praise, and prayers and peace be upon the one after whom there is no prophet, the Mahmoud, the Ahmad, the Mustafa, the most glorious, the supportive messenger, the beloved of the Lord of the worlds, Abi Al-Qasim Muhammad, may God’s prayers and peace be upon him, and his good and pure family, his chosen companions, and those who follow them in goodness until the Day of Judgment. As for after The distinction of the true Islamic religion with the perfection of Islamic law through what came from divine legislation, and this is evident in the speech of God Almighty in His Holy Book, the Sunnah of His Messenger  and the guidance of the Ahl al-Bayt  with the particularity of his collection of all human affairs in all ages and times, as he drew the complete approach in all areas of life, Belief, practical, social, personal, moral, and behavioral, with his worships, transactions, sermons, and guidance, in all that the individual and society needs, for this world and the hereafter.